PENERAPAN EVIDENCE BASED NURSING (EBN) TERAPI MENIUP BALING-BALING DAN SUPER BUBBLES DALAM MENGATASI PENINGKATAN FREKUENSI PERNAFASAN PADA ANAK DENGAN PNEUMONIA - Dinda Nur Aini (2023)
Children are prone to various health problems such as Upper Respiratory Tract Infections and Pneumonia because the child's immune system that is not optimal. Pneumonia can result in airway obstruction, characterized by an increase in respiratory frequency. Blowing propellers and super bubbles is a breath relaxation therapy with play activities that aim to overcome the increase in breathing frequency. The purpose of this study was to analyze nursing care in children with pneumonia who experienced increased respiratory frequency with EBN intervention in the form of propeller blowing therapy and super bubbles. The respondents involved were two people and each was given a propeller blowing intervention and super bubbles. The intervention was carried out for 3 days with a duration of 5 minutes in one day. The frequency of exhalation is calculated by inspection of the movement of the chest wall for one minute. The results of the propeller blowing intervention and super bubbles found a decrease in respiratory frequency by an average of 5x / minute. The author's recommendation is that the implementation of blowing super bubbles can be done outdoors and blowing propellers can be done indoors and outdoors regularly to overcome the increase in respiratory frequency in children.